Binding of teicoplanin and vancomycin to bovine serum albumin in vitro: a multispectroscopic approach and molecular modeling. (22nd April 2013) - Lin, Yongxin; Jiao, Genlong; Sun, Guodong; Zhang, Lili; Wang, Shilong; Liu, Hanchao; Li, Zhizhong
ABSTRACT In this paper, the binding properties of teicoplanin and vancomycin to bovine serum albumin (BSA) were investigated using fluorescence quenching, synchronous fluorescence, Fourier transform infrared (FTIR), circular dichroism (CD) and UV–vis spectroscopic techniques and molecular docking under simulative physiological conditions. The results obtained from fluorescence quenching data revealed that the drug–BSA interaction altered the conformational structure of BSA. Meanwhile, the 3D fluorescence, CD, FTIR and UV–vis data demonstrated that the conformation of BSA was slightly altered in the presence of teicoplanin and vancomycin, with different reduced α‐helical contents. The binding distances for the drug–BSA system were provided by the efficiency of fluorescence resonance energy transfer (FRET). Furthermore, the thermodynamic analysis implied that hydrogen bond and van der Waals' forces were the main interaction for the drug–BSA systems, which agreed well with the results from the molecular modeling study. The results obtained herein will be of biological significance in future toxicological and pharmacological investigation. Copyright © 2013 John Wiley & Sons, Ltd.